Музей-заповедник "Лудорвай" - Тарануха Галина Владимировна (Удмуртия, 2018)
Экземпляры: аб. ЦБ (20200818) / Инвентарный номер: 7906 / Цена: / Сис.шифр: 26.89(2Рос.Удм) / Авт.знак: М 90 / ГРНТИ: 39.19 / ББК: 26.89(2Рос.Удм)